Knowledge, Perceptions, and Prevention Practices among Palestinian University Students during the COVID-19 Pandemic: A Questionnaire-Based Survey - Basma Salameh PhD, RN; Sami Basha PhD; Walid Basha PhD; Jihad Abdallah PhD (SAGE Publishing, 2021)
The purpose of this study is to offer a timely understanding of university students' knowledge, perception, and preventative practices related to COVID-19 in Palestine and to determine affecting factors (gender, region, and type of locality). A cross-sectional design was used and data was collected over 2 weeks in April 2020 through an online survey. A total of 484 surveys were collected from students from different Palestinian universities. Participants showed high levels of knowledge across multiple topics (symptoms and characteristics of COVID-19, prevention practices, and at-risk groups), although respondents were less likely to indicate mask wearing as an effective prevention practice compared to other practices, and almost one-third reported incorrectly that taking antibiotics is effective in preventing COVID-19 infection. Respondents reported the most trust in the Ministry of Health as a source of information, and the least trust in social media. A generally high level of acceptance of government regulations related to the COVID-19 pandemic was found. Given the current global situation and the second wave of infections in Palestine, plans should be in place to disseminate correct information and combat newly-emerging rumors and misinformation through channels that are trusted by the university student population.